Repeated Abortion Affects Subsequent Pregnancy Outcomes in BALB/c Mice - Lv, Fang (Public Library of Science, 2012)
AIM: In this study, we aimed to establish a mouse model of repeated medical termination of pregnancy in order to determine subsequent outcomes. METHODS: A model of mifepristone (RU 486)-induced medical abortion was established in BALB/c mice to facilitate the investigation of the impact of medical abortion on subsequent pregnancies, including litter sizes and newborn birth weights. Pregnant mice were sacrificed to examine midterm pregnancy status, investigate the frequency of fetal resorption, and measure placental function gene expression by real-time PCR and immunohistochemistry. Offspring liver mRNA was harvested for real-time PCR to determine gene expression and assess the effects of abortion on offspring development. RESULTS: Mice subjected to 2 previous medical abortions experienced spontaneous abortions in subsequent pregnancies. Medical abortion caused reduced reproductive capacity and affected placental dysfunction, with reduced expression of tissue factor (TF) and genes encoding proteins involved in metabolic functions relevant to pregnancy, such as 11β-hydroxysteroid dehydrogenase 1/2 (11β-HSD1/2) and glucocorticoid receptor (GR). Reduced expression was also observed for platelet endothelial cell adhesion molecule-1 (CD31) and vascular endothelial growth factor (VEGF). In offspring from subsequent pregnancies, genes involved in lipid metabolism, which may enhance key lipid transcription factors, such as PPARA and PPARG, as well as GR/11β-HSD1, were downregulated in the liver. In addition, the sperm motility of the F1 males reduced. CONCLUSION: Repeated medical abortion impaired the reproductive function of female mice, significantly affecting the outcomes of subsequent pregnancies. The impact of repeated abortions on the offspring of subsequent pregnancies was also noteworthy and deserves further exploration. Thus, this model provides a useful means to study the mechanisms underlying the above phenomena, which will ultimately benefit the health of women and their children.